Effects of Diet with High Polyphenol and Protein Content and Diet with High Boron Content on Microbiota in Obesity - Yilmaz, Feray Cagiran; Turkoglu, Semra (Bentham Science Publ Ltd, 2023)
It is now a known fact that microbiota needs to be regulated in order to prevent obesity, which has become a global public health problem around the world. It is very important to acquire sustainable and easy-to-apply eating habits for microbiota health. Studies show that the type and amount of dietary protein, dietary polyphenol, and boron content can have positive effects on the microbiota. In the light of the research studies examined as a result of this review, it is thought that the microbiota health will improve with the acquisition of a diet with high protein, polyphenol, and boron content, and thus, many chronic health problems related to nutrition, including obesity, can be solved.
Keywords: Microbiota; polyphenol; boron; diet; nutrition; dietary protein